Efficacy of dolutegravir or bictegravir-containing therapy in a real-life cohort of people with HIV-1 sub-subtype A6 - Miłosz Parczewski; Maurizio Zazzi; Kaja Mielczak; Micha Böhm; Olaf Degen; Rolf Kaiser; Francesca Incardona; Anders Sönnerborg; Maarten A.A. van de Klundert (AIDS, 2026)
Objective: The objective of the study was to establish whether HIV-1 sub-subtype A6 (HIV-1A6) is a risk factor for virological failure in people with HIV (PWH) treated with the high genetic barrier integrase strand transfer inhibitors (INSTIs) dolutegravir (DTG) or bictegravir (BIC). Methods: The virological outcome of first-line DTG or BIC-containing antiretroviral therapy (ART) was assessed in 261 people with HIV-1A6 (PWH-1A6) and 1042 people with HIV-1B (PWH-1B) starting treatment between January 2014 and May 2025 with follow-up for at least one year in the EuResist Integrated Database. Results: Most PWH-1A6 were recent migrants from Ukraine. The event rates per 100 person-years follow-up were higher in PWH-1A6 for low-level viremia (LLV, 2.71 vs. 1.71, P = 0.049) and virological failure with more than 1000 HIV RNA copies/mL (4.12 vs. 2.03, P < 0.001) than in PWH-1B. At the end of follow-up, 226/261 (86.6%) PWH-1A6 and 936/1042 (89.8%) PWH-1B had viral load below 50 copies/ml ( P = 0.132). INSTI DRMs were observed in 5/219 (2.3%) available integrase sequences of PWH-1A6, including two cases detected at virological failure with more than 1000 HIV RNA copies/ml and two cases in virologically suppressed PWH-1A6. In total, 12/261 PWH-1A6 discontinued DTG- or BIC-containing ART, including three individuals who were not virologically suppressed at discontinuation. Conclusion: In PWH treated with DTG or BIC-containing first-line ART, LLV and virological failure with more than 1000 HIV RNA copies/ml were observed more frequently in PWH-1A6 than in PWH-1B. However, such events rarely resulted in INSTI resistance or discontinuation of INSTI-containing ART.